2020
DOI: 10.3390/ijerph17186581
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Muscle Quality and Muscle Growth Factor Between Sarcopenic and Non-Sarcopenic Older Women

Abstract: Sarcopenia, an age-related disease, is one of the important health problems in the elderly and the prevalence of sarcopenia is rapidly increased among the Korean population. This study examined the muscle quality and muscle growth factors of elderly women to identify the potential diagnostic tool for sarcopenia. One hundred and thirty-six elderly women, aged over 65 years old, initially enrolled, but only 59 participants who met the criteria (sarcopenic group, n = 27; non-sarcopenic group, n = 32) completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The exact roles of serum myostatin as a biomarker of sarcopenia and its relationship with sarcopenia components (muscle mass and physical function) are uncertain, especially in the community-dwelling elderly. Seo et al [ 13 ] revealed that myostatin was not associated with sarcopenia among 59 elderly female participants. In addition, myostatin levels may reflect skeletal muscle mass, though it functions as suppressing the growth of skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…The exact roles of serum myostatin as a biomarker of sarcopenia and its relationship with sarcopenia components (muscle mass and physical function) are uncertain, especially in the community-dwelling elderly. Seo et al [ 13 ] revealed that myostatin was not associated with sarcopenia among 59 elderly female participants. In addition, myostatin levels may reflect skeletal muscle mass, though it functions as suppressing the growth of skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…This translates into an increased risk of poor quality of life, physical disability, frequent falls and weakness, and death. In this sense, four manuscripts [ 3 , 8 , 9 , 11 ] in this special issue, corresponding to 33.3% of the total, corroborate that muscle loss is the typical consequence of all older adults. The study by Patiño-Villada et al [ 8 ] considers the combination of high muscle mass and shallow fat mass a highly healthy variety.…”
mentioning
confidence: 56%
“…This special edition of the Journal of Environmental Research and Public Health ( IJERPH ) has brought together eleven research manuscripts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and a brief report [ 12 ]. This special issue, entitled “ Sarcopenia, Exercise and Quality of Life ” gathered 12 manuscripts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]; four (33.3%) manuscripts are related to the impact of physical activity concerning sarcopenia [ 4 , 6 , 7 , 10 ]. Two manuscripts were used for the Wii Fit ® games as an intervention tool for physical activity in institutionalized elderly patients [ 4 , 6 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations